Optimalisasi Digital Niche Marketing pada UMKM Kue Tradisional dalam Mewujudkan Desa Wisata Kuliner Berbasis Perempuan - Basrowi, Basrowi; Abdiah Bahar, Ririn Nur; Rohaeni, Nani (Universitas Pahlawan Tuanku Tambusai, 2025)
Magelaran Cilik Village, Serang City, Banten, boasts rich traditional culinary potential, with more than 20 types of specialty cakes managed by local MSMEs. However, most entrepreneurs, particularly female cake artisans, still face serious obstacles, such as limited product innovation, uncompetitive packaging design, low digital literacy, minimal business legality and halal certification, and weak implementation of digital marketing strategies. This Community Service Program (PkM) focuses on optimizing Digital Niche Marketing (DNM) to increase the competitiveness of traditional cake MSMEs while encouraging the establishment of women-based culinary tourism villages. Implementation methods include outreach, product and flavor development training, packaging and branding innovation, strengthening business management, implementing DNM strategies through social media and marketplaces, legality and halal certification assistance, and ongoing monitoring. This activity involves cake artisan associations, village cooperatives, KKM students, and e-commerce partners such as Tokopedia and Shopee. The results showed an 80% increase in production and entrepreneurial management skills, over 90% mastery of niche market-based digital marketing strategies, the fulfillment of halal legality and certification, and the creation of superior products with higher sales value. Furthermore, this program fostered the identity of Magelaran Cilik Village as a women-driven culinary tourism village that contributes to the achievement of the SDGs, particularly in the areas of poverty alleviation, gender equality, and sustainable economic growth.